2017
DOI: 10.2217/fmb-2016-0160
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Zinc Homeostasis in Response to Cryptococcus Neoformans in a Murine Macrophage Cell Line

Abstract: These findings suggest that macrophages may exhibit zinc depletion in response to C. neoformans infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…A growing body of evidence suggests that cryptococcal cells undergo nutritional limitations in infection conditions and must, therefore, express nutrient uptake transporters on the cell surface in order to survive the harsh environment of the infection milieu [ 16 , 33 , 34 , 35 ]. Therefore, we determined the presence of transporter-coding transcripts among the most abundant genes.…”
Section: Resultsmentioning
confidence: 99%
“…A growing body of evidence suggests that cryptococcal cells undergo nutritional limitations in infection conditions and must, therefore, express nutrient uptake transporters on the cell surface in order to survive the harsh environment of the infection milieu [ 16 , 33 , 34 , 35 ]. Therefore, we determined the presence of transporter-coding transcripts among the most abundant genes.…”
Section: Resultsmentioning
confidence: 99%
“…We recently provided evidence that C. neoformans cells experience zinc deprivation inside macrophages ( Dos Santos et al, 2017 ). The main mechanism by which cryptococcal cells acquire zinc is through activity of the Zip1 protein ( Schneider et al, 2015 ; Do et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Zinc restriction has already been characterized for macrophages infected with the fungal pathogens H. capsulatum and C. neoformans . The mechanism by which zinc levels were reduced in macrophages was shown to be dependent on the activity of zinc transporters of the ZnT family ( Winters et al, 2010 ; Subramanian Vignesh et al, 2013a ; Dos Santos et al, 2017 ). At least four lines of evidence allowed us to conclude that amoebae expose cryptococcal cells to a nutritional immunity-like mechanism: (i) assays employing the zinc fluorescent probe ZinPyr-1 revealed that labile zinc levels were reduced in A. castellanii cells exposed to C. gattii ; (ii) transcription levels of some A. castellanii ZnT-coding genes were highly modulated by the presence of cryptococcal cells; (iii) C. gattii cells with reduced growth in zinc-limiting conditions experienced impaired proliferation inside amoeba cells; and (iv) addition of extracellular zinc enhanced intracellular survival of C. gattii cells lacking the major zinc transporter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations